ACCESS CONTROL USING WIRELESS FOR DATA COMMUNICATATION TO DATA TERMINAL - Tan , Jia Min (Universiti Teknologi Petronas, 2010)
The main objective of this project is to develop wireless access control that can be accessed via HTML website using Microchip development board. TCP/IP protocol is used for its wireless technology, using ZeroG module that provides 802.11 standards. Application of wireless access control starts with initialization of hardware and computer through IP address assigned by access point.